Ionic liquid-templated preparation of mesoporous silica embedded with nanocrystalline sulfated zirconia - Ward, Antony J (Springer, 2011)
A series of mesoporous silicas impregnated with nanocrystalline sulphated zirconia was prepared by a sol-gel process using an ionic liquid-templated route. The physicochemical properties of the mesoporous sulphated zirconia materials were studied using characterisation techniques such as inductively coupled optical emission spectroscopy, X-ray diffraction, transmission electron microscopy, energy-dispersive X-ray microanalysis, elemental analysis and X-ray photoelectron spectroscopy. Analysis of the new silicas indicates isomorphous substitution of silicon with zirconium and reveals the presence of extremely small (< 10 nm) polydispersed zirconia nanoparticles in the materials with zirconium loadings from 27.77 to 41.4 wt.%.